Gadolinium‐Encapsulated Graphene Carbon Nanotheranostics for Imaging‐Guided Photodynamic Therapy. Issue 36 (23rd July 2018) - Chen, Hongmin; Qiu, Yuwei; Ding, Dandan; Lin, Huirong; Sun, Wenjing; Wang, Geoffrey D.; Huang, Weicheng; Zhang, Weizhong; Lee, Daye; Liu, Gang; Xie, Jin; Chen, Xiaoyuan
Abstract: Photosensitizers (PS) are an essential component of photodynamic therapy (PDT). Conventional PSs are often porphyrin derivatives, which are associated with high hydrophobicity, low quantum yield in aqueous solutions, and suboptimal tumor‐to‐normal‐tissue (T/N) selectivity. There have been extensive efforts to load PSs into nanoparticle carriers to improve pharmacokinetics. The approach, however, is often limited by PS self‐quenching, pre‐mature release, and nanoparticle accumulation in the reticuloendothelial system organs. Herein, a novel, nanoparticle‐based PS made of gadolinium‐encapsulated graphene carbon nanoparticles (Gd@GCNs), which feature a high 1 O2 quantum yield, is reported. Meanwhile, Gd@GCNs afford strong fluorescence and high T 1 relaxivity (16.0 × 10 −3 m −1 s −1, 7 T), making them an intrinsically dual‐modal imaging probe. Having a size of approximately 5 nm, Gd@GCNs can accumulate in tumors through the enhanced permeability and retention effect. The unbound Gd@GCNs cause little toxicity because Gd is safely encapsulated within an inert carbon shell and because the particles are efficiently excreted from the host through renal clearance. Studies with rodent tumor models demonstrate the potential of the Gd@GCNs to mediate image‐guided PDT for cancer treatment. Overall, the present study shows that Gd@GCNs possess unique physical, pharmaceutical, and toxicological properties and are an all‐in‐one nanotheranostic tool with substantial clinical translation potential. Abstract : Gadolinium‐encapsulated graphene carbon nanotheranostics are synthesized and utilized for imaging‐guided photodynamic therapy. Gd ions play important roles in the formation of graphene structures, unique absorbances, and high singlet oxygen quantum yields. These nanotheranostic tools exhibit low toxicity and can be efficiently excreted by renal clearance from the host after systemic injection.